Piano sonatas, op. 10, nos. 1-3, published by Simrock (later issue) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (N. Simrock; Bonn; Germany)
Piano sonatas no. 5-7, op. 10, no. 1-3, in C minor, F major, and D major; later issue of the Simrock edition with lithographed t.p. decorated in green tint and illustrated with three putti between two pillars.